Knowledge-Behavior Gap on COVID-19 among Older People in Rural Thailand - Vicerra, Paolo Miguel Manalang (Gerontol Geriatr Med, 2021)
This study analyzed the difference between rural and urban older adults in Thailand regarding the relationship between the knowledge and behavior toward the prevention of contracting COVID-19. Path analysis was used to observe if the performance of protective behaviors was affected by the level of knowledge that older people have about the disease. This study used the Impact of COVID-19 on Older Persons in Thailand survey collected across the five regions of the country. Rural residents benefited from community network of village health volunteers who provided information during the pandemic but, they had disadvantages on accessing newer media sources, mainly the internet, for the latest developments on COVID-19. Rural older adults had a higher level of knowledge about COVID-19 than those in urban areas; no difference was observed regarding their behavior to prevent themselves from being infected. The knowledge-behavior gap was viewed as a mechanism of cognitive avoidance because of overwhelming unprecedented information.